Ciliary beat frequency in children with adenoid hypertrophy. Issue 3 (9th January 2020) - Marusiakova, Lucia; Durdik, Peter; Jesenak, Milos; Bugova, Gabriela; Kvassayova, Julia; Oppova, Dasa; Banovcin, Peter
Abstract: Background: Children with adenoid hypertrophy (AH) have impaired respiratory system defense mechanisms, such as mucociliary clearance. We hypothesized that AH negatively affects one of the most important aspects of mucociliary clearance—ciliary beat frequency (CBF) and that adenoidectomy could potentially restore this essential defence mechanism of the airways. This study evaluated the influence of AH and endoscopic adenoidectomy on the CBF of the nasal respiratory epithelium in children. Methods: This prospective study included 64 children with confirmed AH aged 3 to 18 years and 43 age‐ and sex‐matched healthy controls. Nasal CBF was analyzed using a digital high‐speed video microscope and the software application Ciliary Analysis (NI LabVIEW). The preoperative adenoid size was assessed according to Cassano. Clinical symptoms of chronic rhinosinusitis were evaluated using the SNOT‐20 questionnaire. Results: Children with AH had a median CBF of 5.35 ± 1.06 Hz. Six months after surgery, the median CBF was significantly higher (6.48 ± 0.88 Hz; P  < .001) and reached the values of healthy children (6.37 ± 0.71 Hz; P  = .512). The size of the adenoid tissue did not correlate with the CBF. No influence of age or gender on the CBF was found. After adenoidectomy, a significant reduction of the mean total SNOT‐20 score was recorded ( P  < .01). Conclusion: Children with clinically symptomatic AH have impaired mucociliary clearance due to decreased nasal CBF. Removal of hypertrophic adenoid tissue normalizes the CBF and reduces the presence of clinical symptoms of rhinosinusitis.